Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.29309/tpmj/2018.25.04.339
|View full text |Cite
|
Sign up to set email alerts
|

Oral Submucous Fibrosis

Abstract: Objectives: In this study we investigate the effectiveness of lycopene in themanagement of oral submucous fibrosis (OSF) when intralesional steroids also given incombination. Study Design: Cross sectional study. Setting: Dental Section Allied Hospital,Faisalabad. Period: Eight months from September 2016 to April 2017. Methodology: This crosssectional study was initiated after approval from hospital ethical board. Collected Informationwas entered in SPSS computer software version 23 and analyzed for possible re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The TENG can be used as a sensing unit to acquire energy and sense information about the human body. TENG has broad application prospects in sensing fields such as soft wearables and robotics, energy harvesters, and rehabilitation or diagnostics, and it has excellent sensing performance [25][26][27][28][29][30][31][32][33][34][35][36]. It can convert human mechanical energy into electrical energy.…”
Section: Introductionmentioning
confidence: 99%
“…The TENG can be used as a sensing unit to acquire energy and sense information about the human body. TENG has broad application prospects in sensing fields such as soft wearables and robotics, energy harvesters, and rehabilitation or diagnostics, and it has excellent sensing performance [25][26][27][28][29][30][31][32][33][34][35][36]. It can convert human mechanical energy into electrical energy.…”
Section: Introductionmentioning
confidence: 99%
“…In both type of devices, the output is often limited by the change of the material's permeability against temperature and indirectly by its temperature response to the external heat source [8,9]. It is also a fact that not all the heat from the source can be fully utilized due to the limits of heat transfer at a lower temperature, while other parasitic heat losses tend to dominate when operating at higher temperatures [10]. There are also inherent losses in the material, such as the hysteresis that happens during each cycle of magnetization and demagnetization [11].…”
Section: Introductionmentioning
confidence: 99%
“…Rasheed et al [16] observed the boundary layer phenomena for the stagnation point flow of water-based nanofluids with the upshot of the MHD and convective heating on a nonlinear stretching surface. Zeeshan et al [17] examined and executed the multiple-coating assessments of fiber optics utilizing a micropolar convection non-Newtonian third-order liquid in the existence of the Hall effect. Shamsi et al [18] simulated the SEN using a three-dimensional mathematical model based on considerations of the fluid flow, heat transfer and solidification for a better understanding of the process.…”
Section: Introductionmentioning
confidence: 99%